Human Papilloma Virus Increases ΔNp63α Expression in Head and Neck Squamous Cell Carcinoma - Citro, Simona; Bellini, Alice; Medda, Alessandro; Sabatini, Maria Elisa; Tagliabue, Marta; Chu, Francesco; Chiocca, Susanna (Frontiers in Cellular and Infection Microbiology, 2020)
P63, and in particular the most expressed ΔNp63α isoform, seems to have a critical role in the outcome of head and neck cancer. Many studies have been conducted to assess the possible use of p63 as a prognostic marker in squamous cell carcinoma cancers, but the results are still not well defined. Moreover, a clear relationship between the expression of ΔNp63α and the presence of high-risk HPV E6 and E7 oncoproteins has been delineated. Here we describe how ΔNp63α is mostly expressed in HPV-positive compared to HPV-negative head and neck cancer cell lines, with a very good correlation between ΔNp63α mRNA and protein levels.